The dangers of recreational lasers: A case series of retinal injuries - Gaurav Patil; Surendra Wadgaonkar; Ketaki Bhat; Suhas J. Sonawane (Journal of Clinical Ophthalmology and Research)
Six male patients, aged 18–34 years, presented with acute vision loss following accidental exposure to laser light during a religious gathering. Comprehensive ophthalmic examinations, including visual acuity, intraocular pressure, slit-lamp biomicroscopy, dilated fundus examination, fundus photography, and optical coherence tomography, were conducted. Two patients had preretinal hemorrhage, and four exhibited macular-involving subhyaloid hemorrhage, with a median size of two-disc diameters or larger. One patient developed a full-thickness macular hole, requiring surgical intervention. Visual acuity improved from 20/200 to 20/60 after 1 month. This study underscores the significant public health risks associated with recreational laser use and emphasizes the urgent need for stricter safety regulations and public awareness to prevent such potentially sight-threatening ocular injuries.